2003
DOI: 10.1080/00365520310007116
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and LPS‐stimulated production of cytokines and prostaglandin E2 is different in Kupffer cells isolated from the periportal or perivenous liver region

Abstract: Our study suggests that periportal Kupffer cells are responsible for a major part of phagocytosis by the liver. The stronger LPS response of recovered perivenous Kupffer cells suggests a dominant role of these cells in pro-inflammatory events that ultimately may contribute to development of damage in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…LPS absorption in macrophages and other cells is increased under pathophysiological conditions [7]. LPS induces cellular toxicity by involving inflammatory cells and chemical mediators such as reactive oxygen species (ROS), reactive nitrogen species (RNS), pro-inflammatory cytokines and prostaglandins (PGs) [8], [9]. Acetylsalicylic acid (ASA, aspirin), a specific inhibitor of cyclooxygenase (COX) enzyme and a commonly used anti-inflammatory drug, has multiple pharmacological effects which may not be associated with its COX inhibitory activity [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…LPS absorption in macrophages and other cells is increased under pathophysiological conditions [7]. LPS induces cellular toxicity by involving inflammatory cells and chemical mediators such as reactive oxygen species (ROS), reactive nitrogen species (RNS), pro-inflammatory cytokines and prostaglandins (PGs) [8], [9]. Acetylsalicylic acid (ASA, aspirin), a specific inhibitor of cyclooxygenase (COX) enzyme and a commonly used anti-inflammatory drug, has multiple pharmacological effects which may not be associated with its COX inhibitory activity [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liver macrophages are well known for functional heterogeneity 4,6,7,9,13 . Accordingly, different sizes of hepatic macrophages isolated from rat livers have been discussed in the literature 7,12,32 . There was also description of zonal distribution of KCs 4 .…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,9,13 Accordingly, different sizes of hepatic macrophages isolated from rat livers have been discussed in the literature. 7,12,32 There was also description of zonal distribution of KCs. 4 The large ED1 + /ED2 + KCs are located in the liver along the sinusoids while the small ED1 + /ED2 -KCs are found mainly located around the central vein and portal vessels.…”
Section: Differential Expression Of Mrna For Cytokines Ecm Remodelinmentioning
confidence: 99%
“…They are larger and twice as populous in periportal than in centrilobular regions, have more active lysosomes and greater phagocytic activity; however, they secrete fewer superoxide anions. 25,32 Their progenitors are monocytes from the bone marrow which enter the systemic circulation and reach the hepatic tissue, but they also possess the ability for self-renewal. 33,34 Experiments on rodent and human tissue demonstrated that their life span appears to vary from several weeks to one year.…”
Section: K Cs Were Named After Carl Von Kupffer Thementioning
confidence: 99%